Government Policy as a Determining Factor in Improving MSMEs Performance : (Case study of MSMEs in Semarang City) - Shiva Devira Andzani; Sih Darmi Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the role of human resource competencies, entrepreneurial characteristics, innovation, and government policies in improving business performance in MSMEs, especially in the culinary sector of the city of Semarang. This research is a type of quantitative research method using data collection techniques in the form of questionnaires. The population in this study was 3,291 MSMEs. In determining the sample using the purposive sampling method. Of the total 3,291 MSMEs, only 110 Culinary MSMEs were used as respondents in this research. The data collection technique is carried out by distributing questionnaires whose validity and reliability have been tested. The questionnaires are distributed online via google form. The data analysis method used consists of descriptive analysis, outer model evaluation, and inner model evaluation. The data analysis tool in this research uses smartpls 3.0 software. The results of this research show that innovation has a positive effect on business performance. Government policies have a positive effect on business performance. Human resource competency has a negative effect on business performance. Entrepreneurial characteristics have a negative effect on business performance